2011
DOI: 10.1111/j.1600-0838.2010.01283.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance training on endurance capacity and muscle fiber composition in young top‐level cyclists

Abstract: Equivocal findings exist on the effect of concurrent strength (S) and endurance (E) training on endurance performance and muscle morphology. Further, the influence of concurrent SE training on muscle fiber-type composition, vascularization and endurance capacity remains unknown in top-level endurance athletes. The present study examined the effect of 16 weeks of concurrent SE training on maximal muscle strength (MVC), contractile rate of force development (RFD), muscle fiber morphology and composition, capilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
192
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(222 citation statements)
references
References 49 publications
25
192
1
4
Order By: Relevance
“…46,47) In the present study, acetic acid supplementation along with training enhanced exercise-based adaptations in muscle, as reflected by the increased expression of genes involved in energy homeostasis such as LKB1, AMPK, PPARδ, and PGC-1α. Indeed, PPARδ, the primary downstream target of AMPK, is a key regulator of lipid and carbohydrate metabolism in muscle, 48) and targeted activation of PPARδ in muscle leads to increased oxidative muscle fibers and enhanced running endurance.…”
Section: Discussionmentioning
confidence: 49%
“…46,47) In the present study, acetic acid supplementation along with training enhanced exercise-based adaptations in muscle, as reflected by the increased expression of genes involved in energy homeostasis such as LKB1, AMPK, PPARδ, and PGC-1α. Indeed, PPARδ, the primary downstream target of AMPK, is a key regulator of lipid and carbohydrate metabolism in muscle, 48) and targeted activation of PPARδ in muscle leads to increased oxidative muscle fibers and enhanced running endurance.…”
Section: Discussionmentioning
confidence: 49%
“…Recently, it has been reported that concurrent heavy strength training and endurance training in well-trained cyclists result in enhanced cycling performance. [1][2][3][4] Other research groups have previously failed to find a similar positive effect of strength training on performance in trained cyclists. 5,6 In one of our previous articles, cycling performance was determined as the power output in a 5-minute all-out trial performed subsequent to 185 minutes of submaximal cycling.…”
mentioning
confidence: 96%
“…However, although it appears feasible that the previously observed physiological changes induced by peppermint could have possible ergogenic benefits, some of the reported effects have been considerable. Such increases warrant further investigation, particularly when considering other authors have reported much less substantial improvements in cardio-respiratory parameters following a period of intense exercise training (Helgerud et al 2007, Aagaard et al 2011). The effects observed by Meamarbashi and Rajabi (2013) may be the result of a serious flaw in their design, as all participants were tested pre and post supplementation, with no evidence of randomisation.…”
Section: Introductionmentioning
confidence: 99%